Null Subjects in Non-Pro-Drop Languages: The Lens on French - Frascarelli, Mara; Carella, Giorgio (Languages (Basel), 2024)
The contrast between languages such as Italian that allow subjects of tensed sentences to be null (i.e., pro-drop languages) and those like French that do not (i.e., non-pro-drop languages) is a classic issue for comparative syntactic research. Nevertheless, while several studies have been dedicated to pro-drop languages, distinguishing across different types, subject omission in non-pro-drop languages is generally misjudged as a marginal or substandard phenomenon. However, a more careful examination reveals that the occurrence of Null Subjects (NSs) in non-pro-drop languages is associated with distinct semantic and discourse imports. Based on a systematic corpus analysis, this work will confirm that NSs do occur in Colloquial French, especially in the case of expletive subjects. Furthermore, evidence will be provided for a crucial connection between subject omission, expletive types, and the morpho-syntactic categories of person/number for argument pronouns. This pilot work can thus open new perspectives for future research.